Between silences and forgetfulness: the Sergipano Museum of Man, Brazil (2009-2013) (Cadernos de Sociomuseologia, 2016)
Abstract:The Museum of Man in Sergipe (MUHSE), linked to the Department of extension and Community Affairs at the Universidade Federal de Sergipe (UFS), began operations in November 1996, occupying up to 2013 a historic building in Aracaju/SE/Brazil. Your long-term exposure was extracted from the book “Texts for the history of Sergipe” (1991). The Museum found his vocation in educational actions aimed at school audiences (Nunes, 2010: 70). Since May 2, 2011, the Museum has been closed to visitors because of the deterioration of the buildings. The objective of this work, in the midst of the process of new signification whereby the MUHSE passes from 2014, seeks to historicize the processes developed at the institution between 2009 and 2013. Before the new proposal redirects, especially on the new semantics of the institution, wonders how the New Museology or Social Museology could serve as a compass to point the horizon. Between memory and oblivion, wouldn't it be better to make the safeguarding of heritage with respect and attention to the contribution of students, faculty, visitors, managers and neighbors to museum space? The work part of participatory observation of documents (institutional Ordinances and Resolutions) and actions at the Museum studied, as well as readings of Mário Moutinho, Paul Ricoeur, Pierre Nora, among others. Keywords: Museum; oblivion; history; Social Museology; new signification.